Sustainable Development: Learning the Quran Using the Tartil Method - Syafril, Syafrimen; Yaumas, Nova Erlina; Engkizar, Engkizar; Jaafar, Azhar; Arifin, Zainul (AT-TA'LIM, 2021)
This study aims to investigating the effectiveness of using the tartil method in improving students' ability to read the Quran in elementary schools. This study uses a quantitative method with an experimental approach (true experimental pretest-posttest control group design). Data were taken from sixtysix students by means of pre-test and post-test of reading the Quran skills. All students involved are samples of the population which are used as research objects. The research data were then analyzed using descriptive statistics using the Statistical Package for Social Sciences (SPSS Windows 22.0). Overall, the results of the study indicate that the use of the tartil method in learning the Quran is very effective because it can improve students' abilities in reading the Quran. Therefore, the tartil method can be used as an alternative in learning the Quran.